Pengaruh Biaya Pemeliharaan Aset Tetap Terhadap Laba Bersih pada PDAM Kota Cirebon - Raffli Dika Pratama; Arwan Gunawan; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
In the 2016-2020 period, PDAM Cirebon City suffered losses due to water loss caused by pipe leaks, aged water meters, and illegal water theft. This water loss exceeds the tolerance limit of the national water loss rate of 20%, so the company must carry out maintenance activities. Based on these conditions, researchers want to know the development of maintenance costs, the level of net income and the effect of maintenance costs on net income. The sample used is financial statements for five years from 2016.–2020 using quantitative methods. The analytical test used is the classical assumption test, simple linear regressionqanalysis, Pearson correlation analysis, the coefficientpof determination, and perform the t test. The resultswof this study are the development of fixed asset maintenance costs fluctuated, while net income experienced a gradual increasing trend and maintenance costs had an effect but not significant on net income.